PENGGUNAKAN FINTECH PADA MAHASISWA DI LEVEL PERGURUAN TINGGI: MENGUNGKAP PENGARUH KUALITAS PRODUK, PROMOSI DAN KUALITAS PELAYANAN TERHADAP MINAT BELI - Baihaqi, Muhammad Iqbal; Sari Hadi, Nofi Puspita; Pradita, Fatmawati Putri (Jurnal Daya Saing, 2023)
Abstract: This study aims to determine the effect of Product Quality, Promotion and Service Quality on Buying Interest in using Gopay in university students in Bandung City. This study used Quantitative research methods with descriptive and verifiative analysis. The results of this study state that there is an influence of Product Quality, Promotion and Service Quality on Buying Interest in using Gopay. There is an influence of Product Quality on buying interest in using Gopay. There is an influence of Service Quality on purchase interest in using Gopay. Meanwhile, the Promotion does not affect buying interest in using Gopay